Lintas Generasi dalam Tradisi Seblang Olehsari Banyuwangi : Kajian Etnobotani, Konservasi, dan Pewarisan Pengetahuan Lokal di Era Modern - Anas Bagaskara Witanto; Novi Andrilia Pangesti; Nadya Apriyani Putri; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Seblang Olehsari tradition in Banyuwangi is a sacred ritual of the Osing people who use various types of plants as an important part of cultural processions. This research aims to document the use of ritual plants in the Seblang Olehsari tradition and analyze plant conservation efforts and the inheritance of local knowledge between generations in the modern era. This study uses a mixed method approach. Qualitative data was collected through interviews, observations, and documentation of village heads, traditional leaders, Seblang dancers, and the people of Olehsari Village. Quantitative data was obtained through survey techniques using questionnaires on 28 respondents. Quantitative data were analyzed descriptively through intergenerational comparisons to measure the level of local knowledge and its inheritance patterns in the younger and older generations. The results of the study show that there are 33 types of plants that are used in various stages of the Seblang ritual. Quantitatively, the younger generation has a wider range of plant species recognition than the older generation, although a number of plant species are not recognized by both generations. This pattern suggests that local knowledge related to ritual plants is still passed down between generations, mainly through the role of the family as the primary source and direct observation as the dominant transmission mechanism. These findings show that the Seblang Olehsari tradition functions as a biocultural conservation mechanism that plays a role in maintaining the sustainability of the use of ritual plants, as well as supporting the preservation of biodiversity and local knowledge of the Osing people.